A Review on Color Image Fusion Techniques (International Journal of Engineering and Computer Science, 2014)
Image fusion can be defined as the process of extracting the appropriate information from a set of images and then combining them intelligently to form a single composite image with extended information content in order to overcome the limitation of the type and resolution of the hardware sensors capturing images . Image fusion technology can be applied to many areas dealing with images such as medical image analysis, remote sensing, military surveillance, etc. This paper discusses about the problems in color image fusion and   PCA(principal Component Analysis SWT(stationary wavelet transform ,DWT(Discrete Wavelet transform) based image fusion techniques along with the process flow diagram and .